De pedagogo para pedagogo: diálogos a respeito da criança com altas habilidades/ superdotação - Silva, Giana Friedrich Gomes da (2022)
When researching people with High Abilities/Giftedness (HA/G) indicators, the literature presents findings about their identification process, the myths that surround them, and the lack of knowledge of regular teachers about these topics, among others. As we think that students with HA/G attend schools, and that regular class teachers are the ones who work most with them, this work seeks to investigate the practice of pedagogues working in the early years of Elementary School, with regard to HA/G, in order to place them as main agents in working with these students. To answer this question, this qualitative study, with exploratory nature, aims to analyze the pedagogues' narratives about HA/G, in order to recognize how knowledge on the subject is associated with pedagogical practices with these students; intermediate a study and discussion group with teachers for knowledge and paradigm shift on HA/G; and, suggest a teacher training proposal that provides a real impact on their pedagogical practice. Six pedagogues who work both in the classroom and in the management team of a school in the Municipal School System of Santa Maria-RS participated in this study. In order to collect data on their conceptions on the HA/G theme, we organized four meetings using the Focus Group methodology, based on Gatti (2005) and Barbour (2009). Initially, online questionnaires were applied to collect the previous conceptions of each participant. After that, discussions were held on the topic and the results of the questionnaires, enabling the monitoring of posture changes resulting from group interactions. Content analysis was carried out based on studies by Bardin (2011), as it aims to understand the content that is implicit in the participants' speeches. The results showed that specific knowledge about the public with HA/G is not widespread in schools, as teachers demonstrated that they are still based on common sense, and sometimes perpetuate some myths about these students in their speeches (RENZULLI 1978, 2014, 2021; VIRGOLIM, 2014; WINNER, 1998). The analysis of the narratives of pedagogical practices with these students points out that teachers resort to previous experiences to support their practices, which can lead to mistaken evaluations (ALENCAR AND FLEITH, 2005, PÉREZ AND FREITAS, 2014), invisibility of these students (PÉREZ, 2003, SABBAG AND ARANTES-BRERO, 2017), among others. What became evident was the great interest of these teachers in learning more about the subject of HA/G, demonstrating that possibly the lack of knowledge is in the initial and continued training of teacher training courses. Observing the change in attitude regarding knowledge about HA/G, which became more factual and accurate and less mythical on the research participants, we concluded that focus group meetings may be an indication of a valid methodology for practical implementation of more relevant continued education in schools. Based on this, the professional master's product of this research is the structuring of a training proposal based on a focus group: questioning, debating and building knowledge about HA/G through dialogue between teachers.